APPLICATION OF THE HYPNOTEACHING LEARNING METHOD TO IMPROVE SOCIOLOGY LEARNING OUTCOMES AT SMAN 6 KUPANG - Fulgensia Halla; Idris (Sociology Education, Teaching Training and Education Faculty, Muhammadiyah University of Kupang, 2024)
This study aimed to determine the increase in student learning outcomes with the Hypothecating Learning Method in Sociology. The method used in this research is classroom action research (CAR), which includes four stages: planning, implementation, observation, and reflection. Data collection techniques used in this study were observation, learning achievement tests, and documentation. Data analysis techniques using descriptive qualitative analysis. The results of the first cycle test obtained an average value of 100%, with the percentage of students who completed 9 students who had reached KKM as much as 36% and those who had not completed 16 students 64%. However, the results of student tests in cycle I have not yet reached the level of success. However, the research continued to cycle II with an average value of 100% obtained with the percentage of students who did not complete 5 students who had not reached the KKM by 20%, and 20 students who had completed or had reached the KKM by 80% with a total of 25 students. Thus, it can be concluded that applying the Hypothecating method can improve student learning outcomes at SMA Negeri 6 Kupang.